Prolog i epilog. O sztukach Na dnie Maksyma Gorkiego i Franek Rakoczy Władysława Orkana - Mazurek, Halina (Acta Polono-Ruthenica, 2011)
Both of the works unites the same way of exhibition of the people of the margin social. At Gorki at Orkan are there the poor occupants of the hostel which despite the material fall show the interest of the matters of the spirit. They speak about freedom, human nature and the sense of the human existence. In both arts we were found similar figures convergent situations and events. However the differences arises the time of writing both works and their literary convention. The realistic drama On the bottom came into being before the revolution 1905, therefore dominate the atmosphere of the expectation on changes. Orkan writes his poetical drama, simbolistical realistic after 1905 year. Through the defeat of main hero and the fiasco of his plans of improvement of life of the poor shows the end of the hope for better future.